Mecanismos dos núcleos central da amígdala e parabraquial lateral no controle da ingestão de sódio - Franzé, Gláucia Maria Fabrício de Andrade (2015)
The central nucleus of the amygdala (CeA) and the lateral parabrachial nucleus (LPBN) are important areas for the control of sodium appetite. The functional integrity of the CeA is critical to sodium and water intake when LPBN the inhibitory mechanisms are deactivated. Therefore, the aims of this study were to investigate the role of different neurotransmitters of the CeA in the control of sodium and water intake induced by a) sodium depletion and b) after blockade of LPBN inhibitory mechanisms. Male Holtzman rats with stainless steel guide cannula implanted bilaterally only in CeA or both into the CeA and LPBN were used. Sodium (0.3 M NaCl) intake was evaluated in satiated, hyperosmotic and sodium-depleted rats. In sodium-depleted animals, bilateral administration of α2- adrenergic/imidazoline receptor agonist moxonidine (10 nmol) into CeA reduced 0.3 M NaCl and water intake. Moreover, bilateral injections of muscimol (0.25 nmol) into CeA reduced sodium intake without change water intake. Oxytocin receptors activation or its blockade in the CeA, blockade of muscarinic cholinergic receptor or activation of 5HT2A/2C serotonergic receptor into the CeA did not change 0.3 M NaCl or water intake in sodium-depleted animals. Bilateral injections of opioid receptor antagonist naloxone (40 μg) into the CeA did not significantly change 0.3 M NaCl and water intake in sodium-depleted animals. However, sodium and water intake induced by bilateral injections of muscimol (0.5 nmol) into the LPBN in satiated animals were completely abolished after bilateral injections of naloxone (40 μg) into CeA. Furthermore, paradoxical sodium intake observed in rats that received oral gavage with 2 M NaCl (2 ml/rat) combined with bilateral injections of moxonidine (0.5 nmol) in LPBN was also blocked by bilateral naloxone (40 μg) into the CeA. 0.3 M NaCl and water intake induced by bilateral muscimol injections (0.5 nmol) into LPBN in satiated animals were abolished by blocking AT1 angiotensin receptors (losartan - 20 μg) in CeA. In sodium-depleted animals, bilateral injections of losartan (20 μg) into the CeA significantly reduced water intake but did not affect sodium intake. Bilateral injections of the aldosterone antagonist RU 28318 (50 ng) did not change sodium and water intake induced by sodium depletion. Present results suggest that ocitocinergic, cholinergic muscarinic, 5-HT2A/2C serotonergic receptors and aldosterone receptors of the CeA do not participate in the control of 0.3 M NaCl intake induced by sodium depletion. Moreover, present results suggest that GABAergic and α2-adrenergic receptors of the CeA have an inhibitory role for sodium appetite in this situation. Although opioids and angiotensinergic mechanisms of the CeA apparently do not contribute to sodium depletion-induced sodium intake, opioidergic and angiotensinergic mechanisms in CeA are essential for sodium intake when the LPBN inhibitory mechanisms are blockade by LPBN muscimol injection. In addition, opioidergic mechanisms in CeA are also essential for the paradoxical sodium intake by hyperosmotic animals when the inhibitory mechanisms are attenuated by LPBN moxonidine. Therefore, the activation of opioidergic and angiotensinergic receptors of the CeA is required for sodium intake observed after removal or attenuation of LPBN inhibitory mechanisms.